2006
DOI: 10.1016/j.tox.2006.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Early cytotoxic effects of ochratoxin A in rat liver: A morphological, biochemical and molecular study

Abstract: We characterized the overall early effect of chronic ochratoxin A (OTA) treatment on rat liver, analyzing different aspects related to: (i) fibrosis, by measuring collagen content and turnover, and ␣-smooth muscle actin (␣SMA); (ii) oxidative stress and stress response, by analyzing protein carbonylation, superoxide dismutase (SOD) and heat shock protein (HSP70) gene expression; (iii) the possible tumor promoter effect, evaluating cadherin and connexin (CX) mRNA levels. Light microscopy analysis showed no hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 44 publications
4
54
0
Order By: Relevance
“…Nevertheless, this mycotoxin has been shown to affect other target organs as well. It is hepatotoxic in rats and induces hepatocellular carcinomas in mice (NTP 2005;Gagliano et al 2006). Although the liver is not the main target organ for OTA, hepatocytes are exposed to OTA since it has to pass the liver after intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this mycotoxin has been shown to affect other target organs as well. It is hepatotoxic in rats and induces hepatocellular carcinomas in mice (NTP 2005;Gagliano et al 2006). Although the liver is not the main target organ for OTA, hepatocytes are exposed to OTA since it has to pass the liver after intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this mycotoxin is hepatotoxic in rats, probably as a consequence of oxidative stress (Gagliano et al 2006), and OTA induces the formation of hepatocellular tumors in mice (NTP 2005). In 1997, the International Agency for Research on Cancer (IARC) classified OTA as a class 2B carcinogen ("Ochratoxin A is possibly carcinogenic to humans"; IARC 1997).…”
Section: Introductionmentioning
confidence: 99%
“…OTA acts as a carcinogen in the liver by epigenetic mechanisms, which modifying the hepatocyte gap junction apparatus and influencing the expression of specific markers such as alpha-fetoprotein (AFP) (Gagliano et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxy radical can cause oxidative stress and GSH is regarded as an early biological marker of oxidative stress [35] . The MDA production induces alteration of membrane fluidity and increase of membrane fragility [36][37][38] . Early research has shown that LPS could result in oxidative damage, in which the GSH levels and the CAT activity decreased while the MDA levels increased in mice after LPS injection [14] .…”
Section: Discussionmentioning
confidence: 99%